Synthesis of metal-intermetallic laminate (MIL) composites with modified Al3Ti structure and in situ synchrotron X-ray diffraction analysis of sintering process. (5th August 2018) - Lazurenko, D.V.; Bataev, I.A.; Mali, V.I.; Jorge, A.M.; Stark, A.; Pyczak, F.; Ogneva, T.S.; Maliutina, I.N.
Abstract: Al3 Ti-based alloys attract exceptional attention due to their high specific mechanical properties. However, their application is still insufficient due to their low ductility and fracture toughness. Several approaches were previously proposed to address these problems. The first one is stabilization of the cubic modification of titanium trialuminide by alloying. Another approach consists in fabricating metal-intermetallic laminated composites (MIL). In this study, we combined both methods to synthesize the first MIL composite with cubic Al3 Ti interlayers. Copper additions were used to stabilize the cubic modification of Al3 Ti and produce a novel Ti-Al5 CuTi2 MIL composite. First mechanical characterization by indentation tests showed that the binary Al3 Ti intermetallic tended to crack at a load of 0.2 kg while the fracture was not observed in the Al5 CuTi2 layers at least at a load of 1 kg. These results are an indirect evidence of a higher ductility and fracture toughness of the composite with cubic Al3 Ti compared to tetragonal one. The sequence of the phase transformations in the Al-Ti-Cu system was studied using in situ synchrotron X-ray radiation diffraction. The formation of Al5 CuTi2 occurred via several intermediate stages including eutectic melting of Al and Cu and the formation of binary AlCu and Al3 Ti compounds. Graphical abstract: Unlabelled Image Highlights: Multilayer composites with Al3 Ticubic layers were firstly synthesized by doping Al3 Ti with Cu during the synthesis. Composites with the cubic Al3 Ti demonstrate the improved fracture toughness compared to the ordinary tetragonal one. During formation of Al3 Ticubic the following reactions proceeds: Al+Ti+Cu → AlCu+Al3 Ti+Ti → Ti+AlCuTi+Al3 Ticubic .